ADEQUAÇÃO DE MODELOS PROBABILÍSTICOS À EVAPOTRANSPIRAÇÃO DE REFERÊNCIA NO SUBMÉDIO DO VALE DO RIO SÃO FRANCISCO - Santiago, Edgo Jackson Pinto; Silva, Frank Gomes; Silva, Antonio Samuel Alves da; Cantalice, José Ramon Barros; Cunha Filho, Moacyr; Aguiar, José Domingos Albuquerque (IRRIGA, 2021)
ADEQUAÇÃO DE MODELOS PROBABILÍSTICOS À EVAPOTRANSPIRAÇÃO DE REFERÊNCIA NO SUBMÉDIO DO VALE DO RIO SÃO FRANCISCO EDGO JACKSON PINTO SANTIAGO1; FRANK GOMES-SILVA 1; ANTONIO SAMUEL ALVES DA SILVA1; JOSÉ RAMON BARROS CANTALICE1; MOACYR CUNHA FILHO1 E JOSÉ DOMINGOS ALBUQUERQUE AGUIAR1 1 Departamento de Estatística e Informática-DEINFO, Programa de Pós-Graduação em Biometria e Estatística Aplicada-PPGBEA, Universidade Federal Rural de Pernambuco-UFRPE, Rua Dom Manoel de Medeiros s/n, Dois Irmãos, CEP: 52.171.900, Recife, Pernambuco, Brasil. edgoj@hotmail.com, franksinatrags@gmail.com, antonio.sasilva@ufrpe.br, cantalice21@hotmail.com, moacyr2006@gmail.com, aguiar.domingos@gmail.com. 1 RESUMO A evapotranspiração consiste no processo de perda de água do solo, da planta, e é fundamental para produção vegetal, constituindo uma das principais variáveis agrometeorológicas. Apesar disso, são escassos trabalhos que relacionam adequabilidade de distribuições de probabilidade a dados de evapotranspiração. O objetivo desse trabalho foi testar a aderência de diferentes distribuições de probabilidade à dados de evapotranspiração de referência, selecionando as mais adequadas para este fim. Esse estudo foi realizado com dados de evapotranspiração de referência obtidos pelas estações meteorológicas da Universidade Federal do Vale do São Francisco (UNIVASF) em Petrolina, PE e Juazeiro, BA. Foram ajustadas as distribuições Gama, Weibull, Log-Normal, Beta, Exponencial, Log-Logística e Log-Logística Exponenciada. Os maiores p-valores foram obtidos para as distribuições Log-Logística e Log-Logística Exponenciada, possivelmente devido à leve assimetria positiva destas aos dados de evapotranspiração. Pelo teste da razão de verossimilhanças, a distribuição Log-Logística Exponenciada adequou-se mais aos meses de janeiro, agosto e dezembro em Juazeiro e Petrolina, somando-se a esta última o mês de novembro. As distribuições Log-Logística e Log-Logística Exponenciada foram as mais adequadas para modelar a evapotranspiração. A partir dessas distribuições, foram estimados valores de evapotranspiração para diferentes níveis de probabilidade, sendo janeiro o mês com maior demanda hídrica provável. Palavras-chave: transpiração, evaporação, demanda hídrica, distribuição log-logística, irrigação. SANTIAGO, E. J. P.; GOMES-SILVA, F.; SILVA, A. S. A.; CANTALICE, J. R. B.; CUNHA FILHO, M.; AGUIAR, J. D. A. ADJUSTMENT OF PROBABILISTIC MODELS TO THE REFERENCE EVAPOTRANSPIRATION IN THE SUB-MEDIUM OF SÃO FRANCISCO RIVER VALLEY 2 ABSTRACT Evapotranspiration is the process of water loss from soil and plant surfaces, and it is essential for plant production, constituting one of the main agrometeorological variables. Nevertheless, there are few studies that relate the adequacy of probability distributions to evapotranspiration data. The objective of this work was to test the adherence of different probability distributions to reference evapotranspiration data by selecting the most suitable ones for this purpose. This study was carried out with daily evapotranspiration reference data obtained by the meteorological stations of the Federal University of Vale of São Francisco (UNIVASF) in Petrolina, PE and Juazeiro, BA. The Gamma, Weibull, Log-Normal, Beta, Exponential, Log-Logistics and Exponentiated Log-Logistics distribution were adjusted. The highest p-values ​​were obtained for the Log-Logistics and Exponentiated Log-Logistics distributions. The highest p-values were obtained for the Log-Logistics and Exponentiated Log-Logistics distributions, possibly due to the slight positive asymmetry of those to the evapotranspiration data. By testing the likelihood ratio, the Exponentiated Log-Logistics distribution was more suitable for the months of January, August and December in Juazeiro and Petrolina, adding to the latter the month of November. The Log-Logistics and Exponentiated Log-Logistics distributions were the most suitable to model evapotranspiration. From these distributions, evapotranspiration values ​​were estimated for different levels of probability, with January being the month with the highest probable water demand. Keywords: transpiration, evaporation, water demand, log-logistics distribution, irrigation.